THE ECONOMIC IMPACT OF GEOPOLITICAL TENSIONS ON GLOBAL TRADE AND SUPPLY NETWORKS - Kelmendi, Jeton; Beqiri, Agim; Shuajibi, Elmedina; Talibzade, Orkhan; Ketners, Karlis (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
Geopolitical tensions significantly impact global supply chains, disrupting trade, logistics, and economic stability. This study examines the economic resilience of Kosovo, Belgium, and Azerbaijan, which face diverse geopolitical challenges due to their differing geographical positions, economic structures, and international trade networks. The research aims to identify key factors influencing economic sustainability in the face of geopolitical disruptions and propose strategies for mitigating risks. A comparative analysis was conducted using qualitative and quantitative methods to assess the impact of geopolitical conflicts, sanctions, and trade restrictions on global supply chains. The study integrates statistical trade data, policy analyses, and case studies to evaluate the geopolitical pressures affecting logistics and international commerce. Findings reveal that economic stability and resilience to geopolitical risks depend on a country’s ability to adapt through infrastructure development, trade diversification, and international cooperation. Kosovo struggles with trade limitations due to partial international recognition and regional instability. Belgium faces supply chain disruptions due to Brexit and EU sanctions against Russia but benefits from strong institutional frameworks. Azerbaijan, while strategically positioned as an energy supplier, must navigate regional tensions and shifting global trade alliances. This study provides novel insights by comparing countries with different economic structures and geopolitical vulnerabilities, highlighting diverse adaptation strategies. The results underscore the need for proactive policy measures, investment in infrastructure, and diversification of trade partnerships to strengthen resilience. These findings offer valuable implications for policymakers and businesses seeking to mitigate geopolitical risks and enhance global supply chain stability.